Singular solitons and other solutions to a couple of nonlinear wave equations - İnç, Mustafa; Ulutas, Esma; Biswas, Anjan (Iop Publishing Ltd, 2013)
This paper addresses the extended (G' / G)-expansion method and applies it to a couple of nonlinear wave equations. These equations are modified the Benjamin-Bona-Mahoney equation and the Boussinesq equation. This extended method reveals several solutions to these equations. Additionally, the singular soliton solutions are revealed, for these two equations, with the aid of the ansatz method.
Keywords: (G ' / G)-expansion method; travelling wave solutions; singular soliton; mBBM and Boussinesq equations